Unloading the catch - Mumbai Archive Project Team (Jio Institute, 2024)
Koli fishermen bring freshly caught fish to designated landing centres, such as fishing docks, harbours, or beaches. Once ashore, they sort the fish based on their species, size, and quality, a task typically carried out by the fishermen or their family members.